Gout and diabetes: a common combination. Issue 1089 (10th May 2016) - Collier, Andrew; Stirling, Angus; Cameron, Lyall; Hair, Mario; Crosbie, David
Abstract: The aims of this cross-sectional study were to compare metabolic parameters in people with gout and diabetes with gout only and type 2 diabetes mellitus (T2DM) only. Fifty General Practices in NHS Ayrshire and Arran (population 340 377) contributed data. The sample was split into three groups, those with both gout and T2DM, those with gout only and those with T2DM only. The prevalence of gout in Ayrshire and Arran was 2.65%. The prevalence of gout in people with type 1 and 2 diabetes was 1.90% (p=0.30) and 10.12% (p<10 −5 ), respectively. Patients with both conditions were significantly more likely to be male (p<10 −5 ), older (p<10 −5 ), have a higher mean body mass index (p<0.001), higher triglycerides (p<10 −4 ), lower mean total, high-density lipoprotein- and low-density lipoprotein cholesterol (p<10 −5 ), lower estimated glomerular filtration rate (p<0.001), neuropathy (p=0.02), lower haemoglobin (p<0.001), to be prescribed more medications (p<10 −5 ) and less likely to smoke (p<0.01). There was an association between lower haemoglobin A1c and increased prevalence of gout (p<0.001). 42.4% of patients with gout alone and 36.2% of those with both gout and diabetes had a urate measure. This study defines much more clearly the association between gout and T2DM. Of interest, in terms of lifestyle, both better glycaemic control and smoking are associated with a higher prevalence of gout.